Perbedaan Penambahan Diclovenac Topikal Pada Intervensi IRR dan Aktif Exercise Terhadap Pengurangan Nyeri OA Lutut (Lembaga Penerbitan Universitas Esa Unggul, 2009)
The goal of this research is to know difference of Diclofenac topical increment on IRR and active exercises to decrease painful on the knee of Osteoarthritis. Total sample of this research are 12 people, devide in 2 gruops of treatment, the group I award diclovenac topical IRR and active excercise, as for groups II award IRR and active excer-cise, the measurmant device to mate the pain degree with VAS (visual analog skale).The research methodology is experimental quasi. It is means to know the influence of a treatment towards the object of the research. The result of Wicoxon tes to the team’s research one occur painful value influential descent level between before and after treatment with value 29.833 unit VAS, with P value 0,028. It means that diclofenac topical increment on infra red radiation intervention and active exercises have significant influence to decrease painful on knee of Osteoarthritis. On team’s research two from Wil-coxon experiment gotten by decreasing painful between before and after treatment with value 25.833 unit VAS value with P value 0,028 that meant giving IRR and active exercises proven on decreasing painful value on the knee of Osteoarthritis. From the Mann-Whitney tes it is known that P value 0,297 is means that there is no significan difference in lessening pain between treatment’s team one and treatment’s team two. So these two methods can be used as intervention method for decreasing painful on the knee of Osteoarthritis problem.Keywords: Diclofenac Topical, Exercise, Osteoartritis